Pricing Liquidity Risk with Heterogeneous Investment Horizons - Beber, Alessandro; Driessen, Joost; Neuberger, Anthony; Tuijp, Patrick (Journal of Financial and Quantitative Analysis, 2021)
Abstract We develop an asset pricing model with stochastic transaction costs and investors with heterogeneous horizons. Depending on their horizon, investors hold different sets of assets in equilibrium. This generates segmentation and spillover effects for expected returns, where the liquidity (risk) premium of illiquid assets is determined by investor horizons and the correlation between liquid and illiquid asset returns. We estimate our model for the cross-section of U.S. stock returns and find that it generates a good fit, mainly due to a combination of a substantial expected liquidity premium and segmentation effects, while the liquidity risk premium is small.